VICTIM’S RIGHTS AND THE CRIMINAL JUSTICE SYSTEM OF INDIA - Hans Kumar Sharma (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2022)
Victims of crime are covered, aided, restituted, and paid by applicable laws and actions in various countries including India. However, in India, victims of crime play a minor role in the criminal justice system. One of the many changes proposed in recent years to improve the criminal justice system is one that calls for a victim-oriented approach to criminal justice Administration. A significant emphasis was placed in the Report of the Committee on Reforms of the Criminal Justice System, headed by Justice V. S. Malimath, on the need to provide "justice to victims of crime." The Committee stated that victim compensation is a legal requirement in all violent crimes, regardless of whether the perpetrator is apprehended, convicted, or acquitted. According to the UN Declaration of Basic Principles of Justice for Victims, “victims are persons who have suffered damage, including physical or mental injury, economic loss, or significant deprivation of their fundamental rights, as a result of actions or omissions that are in violation of criminal laws operational within Member States, including those laws preventing criminal abuse of power." In general, every sound criminal justice administration recognizes two forms of protections for victims: first, the right to engage in criminal proceedings, and second, the right to demand restitution from the criminal court or the state for injuries sustained. Apart from Several clauses in the Indian Constitution and other legislature of the India the Indian Supreme Court has played a crucial role in creating compensatory jurisprudence for victims. On the other hand various schemes to improve victim justice have been framed by the Indian government over the last decade, but their execution at the grassroots level has often been challenged due to procedural lapses and there is a need to be focused by society and law makers. KEYWORDS: Victims, Crime, Criminal Justice System, Rehabilitation